The Correlation Between Questioning Strategies And Student's Focus (A Study of Teachers in East Lombok) - Hanofi Harianto; Abdul Hakim Bin Abdullah; Taufiq Kurniawan (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
In the learning process, students’ ability to stay focused is a crucial factor in achieving optimal learning outcomes. The teacher’s teaching strategies, including questioning strategies, play an important role in building students’ focus in the classroom. This study aims to identify and analyze the correlation between the questioning strategies implemented by the teacher and students’ learning focus in the classroom Methodology: This quantitative correlational study employed descriptive and inferential analyses with random sampling. The sample consisted of 113 teachers, including 72 males and 41 females, who taught eleventh-grade students in private schools in East Lombok, NTB. Data were collected using an online form, and the reliability of the instrument was tested using Cronbach’s Alpha. The data analysis procedure was conducted through Spearman correlation analysis. Findings: The research results found a correlation value of r = 0.531 with a significance level of 0.000 (p < 0.05). Conclusion: The research results indicate that there is a positive and significant relationship between the questioning strategies used by the teacher and the students' level of focus in learning. This suggests that the more effective the questioning strategies implemented by the teacher, the higher the students' level of focus in the classroom. Keywords: questioning strategies, student's focus